JEJAHITAN: ETHNOPEDAGOGICAL STUDY IN BALINESE CULTURE - Jayantika, I Gusti Agung Ngurah Trisna; Suastra, I Wayan; Arnyana , Ida Bagus Putu (Indonesian Journal of Educational Development (IJED), 2024)
Mejejahitan is an activity to obtain the shapes of pieces of leaf material. The product of this activity is called jejahitan. This research is a qualitative descriptive study. The aim of this research is to determine the mathematical concepts that exist in Balinese jejahitan and the potential for their use in the mathematics learning process. The subjects of this research were three mothers from Dalung village. The data in this research was analyzed through three stages, namely data reduction, data presentation and data conclusion. Studies on Mathematics learning contained in jejahitan include squares, rectangles, trapezoids and circles. The geometric elements contained in this jejahitan can be used as a learning resource, especially those related to the elements, properties and fold symmetry of squares, rectangles, trapezoids and circles.